Formação docente no Ensino Superior: um estudo da formação dos docentes atuantes no curso de Licenciatura em Ciências Química e Biologia do ICET/UFAM - Fonseca, Marlete Miranda (Brasil, 2024)
This study aims to analyze the training of teachers in the Science degree Course: Chemistry and Biology who work at the Institute of Exact Sciences and Technology of the Federal University of Amazonas to work with deaf students. To achieve this goal, the research examined the teachers’ profiles and academic backgrounds. This revealed that the teachers have not received the necessary training in Libras and that there is no adequate training for deaf students in their higher education courses. This research was characterized as qualitative, exploratory, and analytical. It was carried out using field research, through data collection, a bibliographic review and we used semi-structured interviews as the collection instrument. Questionnaires were applied using Google Forms and bibliographical research was carried out to find reputable authors with a comprehensive view of the training of educators as professionals. Given the results analyzed, we can see that the teachers have a fragile background in sign language, only one teacher took Libras as an undergraduate, they have never taught deaf students, they have never taken a voluntary Libra course and around 18% have no interest in learning this language. In this way, it is possible to highlight the importance of teaching that qualifies teachers so that they can be prepared to receive their students, in addition to discussing inclusion in degree courses. Thus, the questions raised about the training of teachers in libras in higher education can serve as food for thought for teachers, and as a proposal to revise the laws that govern the teaching of libras in our country, reducing the harmful effects of teaching practices.